TRADITIONAL MEDICINAL PLANTS OF RAJASTHAN USED IN TRIBAL MEDICINE : A REVIEW: Life Science-Ethono Botany - MEGHENDRA SHARMA; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2013)
Around seven percent of tribal population of India lives in Rajasthan. Ethnobotany can be defined as the total natural and traditional relationship and the interactions between man and his surrounding plant wealth from times immemorial, due to sheer, necessity, intuition, observation and experimentation. Ethnobotany of India might is among the earliest in the world and all traditional systems of medicine had their roots in ethnobotany. Rajasthan has rich cultural diversity and biodiversity. Present paper presents use of medicinal plants by tribal people in general and Rajasthan in particular.